2017
DOI: 10.1098/rsos.170084
|View full text |Cite
|
Sign up to set email alerts
|

The impact of induced anxiety on affective response inhibition

Abstract: Studying the effects of experimentally induced anxiety in healthy volunteers may increase our understanding of the mechanisms underpinning anxiety disorders. Experimentally induced stress (via threat of unpredictable shock) improves accuracy at withholding a response on the sustained attention to response task (SART), and in separate studies improves accuracy to classify fearful faces, creating an affective bias. Integrating these findings, participants at two public science engagement events (n = 46, n = 55) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…For example, participants diagnosed with negative mood disorders more accurately inhibit responding on a cognitive task when threatened with unpredictable shock, suggesting state stress enhances behavioral inhibition (Mkrtchian et al, 2017). Aylward et al (2017), however, failed to find an effect of threat of unpredictable shock on behavioral inhibition in a non-clinical sample, indicating that behavioral inhibition under stress identifies clinical, but not sub-clinical, populations. We therefore might expect not to see behavioral inhibition in a (presumably) sub-clinical group of monkeys under baseline conditions.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…For example, participants diagnosed with negative mood disorders more accurately inhibit responding on a cognitive task when threatened with unpredictable shock, suggesting state stress enhances behavioral inhibition (Mkrtchian et al, 2017). Aylward et al (2017), however, failed to find an effect of threat of unpredictable shock on behavioral inhibition in a non-clinical sample, indicating that behavioral inhibition under stress identifies clinical, but not sub-clinical, populations. We therefore might expect not to see behavioral inhibition in a (presumably) sub-clinical group of monkeys under baseline conditions.…”
Section: Discussionmentioning
confidence: 81%
“…Additional factors that may have influenced performance on the touch-screen task include mismatching effects (e.g., touch a negative stimulus to gain a positive reward, which has been shown to exacerbate the impact of transient emotion states on task performance (Raoult et al, 2017), and influence of attentional processes (Bar-Haim et al, 2007). For example, Aylward et al (2017) found faster responses by human participants taking part in a computer task to fearful faces compared to happy faces, which was independent of affective state (threat of electric shock). The authors attributed this speeding of response to attentional capture by negative stimuli.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, as in the majority of the threat of shock studies (i.e. 60 , 61 ), aversive stimuli were delivered only in threat blocks while participants did not receive any stimulation in safe ones. This difference in stimulation could be involved in the observed SCL differences.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, neuropsychology and cognitive neuroscience studies have revealed that the medial prefrontal regions [including the anterior cingulate cortex (ACC)] are crucial substrates of the human anxiety circuitry (Sehlmeyer et al, 2009) and that deficits in these areas are associated with impaired inhibition control (Sehlmeyer et al, 2010). Although previous studies have shown that individuals with state anxiety (e.g., experimentally induced anxiety; see Aylward et al, 2017), anxiety with substance use (Karch et al, 2007), and clinical anxious patients (Grillon et al, 2017) have deficits in response inhibition, the question remains on whether and at what extent anxiety-related personality traits (e.g., trait anxiety) can also modulate response inhibition. Recent studies have demonstrated that trait anxiety interrupts top-down goal-driven processes such as response inhibition, resulting in failures in the inhibition function that enable executive control over prepotent motor responses (Pacheco-Unguetti et al, 2012;Su-Hao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%